Aberrant Expression of CD Markers in Acute Leukemia with Hematological Parameters Correlation: A Single Center Experience - Monika Sharma; Nutan Dixit; Taruna Bansal; Vijay Kumar; Sai Jyoti (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Immunophenotyping by flowcytometry improves both the accuracy and reproducibility of an acute leukemia (AL) diagnosis. The morphologically similar blast cells can be easily differentiated by immunophenotyping based on expression and different CD (cluster of differentiation) markers. It also plays a crucial role in the identification of aberrant antigens. The present study was conducted to determine the frequency of aberrant phenotypes in newly diagnosed cases of acute leukemia and its correlation with hematological parameters. Methods: We retrospectively investigated the phenotype of blast cells from 72 patients with acute leukemia diagnosed over a one and half year period. Diagnosis of acute leukemia was based on morphology, cytochemistry, and immunophenotyping by flow cytometry. Results: Out of the total 72 cases of Acute leukemia, 40 (55.6%) cases showed aberrant expression. 12/27 cases (44.4%) of AML and 28/45 cases (62.2%) of ALL showed aberrant phenotypes in the present study. Aberrant expression of CD7, 6/27 cases (22.2%) was very frequent in AML. Among the ALL cases, CD13, 14/45 cases (31.1%) were most commonly expressed. The mean total leukocyte count (TLC) and percentage of blasts in peripheral blood were significantly higher in AML and ALL cases with aberrant phenotypes as compared to their conventional phenotypes with no aberrancy. Conclusions: It is of clinical importance to detect aberrant phenotypes for accurate diagnosis and when looking for minimal residual disease during morphologic remission. In addition, aberrant phenotypes in AML and ALL cases are associated with unfavorable hematological features in our study.